ECONOMETRIC ANALYSIS OF EVALUATION OF INVESTMENT PROJECTS IMPLEMENTED IN THE REPUBLIC OF KARAKALPAKSTAN - Bahodirjon Bayhonov; Saida Abdurakhimova; Guzal Adilova (Scholar Express Journals, 2023)
In the article, an econometric analysis of the evaluation of investment projects was carried out, in which the impact of the investments made within the framework of the projects currently being implemented in the Republic of Karakalpakstan on the gross regional product was analyzed. For this purpose, first of all, the research works conducted by foreign and CIS scientists in this field were studied, and process change models were created using the econometric modeling methodology in our research. Proposals and recommendations for effective implementation of investment projects and their evaluation are described using the results of the analysis.
Keywords: investment project; capital investment; efficiency